Blood parameters of emperor penguin Aptenodytes forsteri chicks at their northernmost Antarctic colony - D'amico, Veronica Laura; Libertelli, Marcela; Coria, Néstor Rubén; Bertellotti, Néstor Marcelo
The emperor penguin (Aptenodytes forsteri) is one of the penguins most threatened by global warming therefore, it is important to monitor physical condition of individuals, especially in the colonies spread further north where the effect of climate change is greater. Here, we present blood and biochemical markers of the general physical condition related to health, nutrition and immune function of emperor penguin chicks at Cerro Nevado/Snow Hill Island, Antarctica, the northernmost colony of their distribution, during the winter season of 2014. We determined the leukocyte counts, the heterophil / lymphocyte ratio and the concentrations of glucose, cholesterol and triglycerides in emperor penguin chicks. These data constitute the first report in chicks of emperor penguins at this location. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Libertelli, Marcela. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina